The Research and Impact Evaluation of Eco-Driving Strategy on Specific Energy Consumption in a Passenger Vehicles - Gorzelanczyk, Piotr; Piatkowski, Piotr (Communications - Scientific Letters of the University of Zilina, 2022)
The article presents the results of an assessment of the impact of Eco-driving on the achieved emission parameters and performance characteristics of vehicles, with a particular focus on energy efficiency. The first part of the article presents the main principles of Eco-driving and then presents the results of experimental tests carried out on two vehicles powered by conventional fuel in the form of gasoline and substitute (unconventional) fuel in the form of LPG. The vehicles were operated under different traffic conditions. Based on the analysis of the experimental results, final conclusions were formulated. The analysis of the test results made it possible to demonstrate differences in the on-road energy consumption of the vehicles depending on the driving technique used and, in addition, the results obtained were compared to the energy intensity of electric vehicles as reported by their manufacturers.
Keywords: eco-driving strategy; specific energy consumption (SEC) vehicle